Partial Amniote Sex Chromosomal Linkage Homologies Shared on Snake W Sex Chromosomes Support the Ancestral Super-Sex Chromosome Evolution in Amniotes - Singchat, Worapong; Ahmad, Syed Farhan; Sillapaprayoon, Siwapech; Muangmai, Narongrit; Duengkae, Prateep; Peyachoknagul, Surin; O’Connor, Rebecca E.; Griffin, Darren K.; Srikulnath, Kornsorn (Frontiers in Genetics, 2020)
Squamate reptile chromosome 2 (SR2) is thought to be an important remnant of an ancestral amniote super-sex chromosome, but a recent study showed that the Siamese cobra W sex chromosome is also a part of this larger ancestral chromosome. To confirm the existence of an ancestral amniote super-sex chromosome and understand the mechanisms of amniote sex chromosome evolution, chromosome maps of two snake species (Russell’s viper: Daboia russelii [DRU] and the common tiger snake: Notechis scutatus [NSC]) were constructed using bacterial artificial chromosomes (BACs) derived from chicken and zebra finch libraries containing amniote sex chromosomal linkages. Sixteen BACs were mapped on the W sex chromosome of DRU and/or NSC, suggesting that these BACs contained a common genomic region shared with the W sex chromosome of these snakes. Two of the sixteen BACs were co-localized to DRU2 and NSC2, corresponding to SR2. Prediction of genomic content from all BACs mapped on snake W sex chromosomes revealed a large proportion of long interspersed nuclear element (LINE) and short interspersed nuclear element (SINE) retrotransposons. These results led us to predict that amplification of LINE and SINE may have occurred on snake W chromosomes during evolution. Genome compartmentalization, such as transposon amplification, might be the key factor influencing chromosome structure and differentiation. Multiple sequence alignments of all BACs mapped on snake W sex chromosomes did not reveal common sequences. Our findings indicate that the SR2 and snake W sex chromosomes may have been part of a larger ancestral amniote super-sex chromosome, and support the view of sex chromosome evolution as a colorful myriad of situations and trajectories in which many diverse processes are in action.